The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2009
DOI: 10.2165/00023210-200923030-00002
|View full text |Cite
|
Sign up to set email alerts
|

Management of Patients Presenting with Acute Psychotic Episodes of Schizophrenia

Abstract: The initial management of patients with schizophrenia presenting to psychiatric emergency departments with an acute psychotic episode requires rapid decisions to be made by physicians concerning the treatment of individuals who are likely to be relatively uncooperative, agitated and lacking insight. The treatment decision must be adapted to the individual characteristics and needs of each patient. This article reviews the issues from the perspective of the initial management of acute psychosis as it is current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 115 publications
1
25
0
Order By: Relevance
“…However, there are few studies with which to make meaningful comparisons. A similar trend was previously reported from earlier studies (Thomas et al 2009) on mortality of reactive psychoses. It was reported that there was a significantly raised mortality risk in reactive psychosis, and suicide was the largest cause of premature death.…”
Section: Mortality In Atpdsupporting
confidence: 91%
See 2 more Smart Citations
“…However, there are few studies with which to make meaningful comparisons. A similar trend was previously reported from earlier studies (Thomas et al 2009) on mortality of reactive psychoses. It was reported that there was a significantly raised mortality risk in reactive psychosis, and suicide was the largest cause of premature death.…”
Section: Mortality In Atpdsupporting
confidence: 91%
“…Similarly, a study by Perris (1974) found that patients with cycloid psychosis on continuous lithium treatment experienced fewer repeat episodes. General treatment recommendations for patients presenting with their first episode of psychosis, including psychotic disorders with acute onset, include a comprehensive assessment to evaluate comorbidities and rule out organic and substance-induced causes (Thomas et al 2009). A typical antipsychotics, often at low initial doses, are recommended as the first line of medication treatment, with continuation of treatment for 1 year (Jabs et al 2002).…”
Section: Non-pharmacological Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Second-generation (atypical) antipsychotics are currently the mainstay of therapy for both disorders and include compounds such as clozapine, olanzapine, quetiapine, risperidone, and aripiprazole. These second-generation compounds are associated with less severe extrapyramidal symptoms but are associated with a metabolic syndrome (dyslipidemia, insulin resistance, pronounced weight gain, and elevations in blood pressure), which can unfavorably alter the benefit-risk ratio (Gründer et al, 2009;Kim et al, 2009;Meyer and Stahl, 2009;Thomas et al, 2009). The metabolic syndrome and obesity are estimated to occur in 33% of patients with schizophrenia and bipolar disorders.…”
Section: Future Directionsmentioning
confidence: 99%
“…12,13 Moreover, some research suggests that patients receiving atypical antipsychotics have more favorable subjective responses to their current medication than those receiving conventional medications. [14][15][16] However, other studies report no difference or suggest patient characteristics may be responsible for differences in adherence rather than type of medication.…”
Section: Introductionmentioning
confidence: 99%